2019
DOI: 10.1021/jacs.9b04491
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Abstraction/Addition Tunneling Reactions Elucidate the Interstellar H2NCHO/HNCO Ratio and H2 Formation

Abstract: Formamide (H2NCHO) is the smallest molecule possessing the biologically important amide bond. Recent interstellar observations have shown a strong correlation between the abundance of formamide and isocyanic acid (HNCO), indicating that they are likely to be chemically related, but no experiment or theory explains this correlation satisfactorily. We performed H + H2NCHO reactions in a para-hydrogen quantum-solid matrix host and identified production of H2NCO and HNCO from hydrogen-abstraction reactions. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
97
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 46 publications
11
97
0
1
Order By: Relevance
“…In order to demonstrate the applicability of this method, we briefly discuss the H abstraction and addition reactions of formamide (H 2 NCHO) and isocyanic acid (HNCO) in solid para-H 2 . (See details of this investigation in Haupa et al (2019)). H 2 NCHO, the smallest molecule possessing an amide group, was first detected toward Sagittarius B2 almost 50 years ago (Rubin et al (1971)).…”
mentioning
confidence: 99%
“…In order to demonstrate the applicability of this method, we briefly discuss the H abstraction and addition reactions of formamide (H 2 NCHO) and isocyanic acid (HNCO) in solid para-H 2 . (See details of this investigation in Haupa et al (2019)). H 2 NCHO, the smallest molecule possessing an amide group, was first detected toward Sagittarius B2 almost 50 years ago (Rubin et al (1971)).…”
mentioning
confidence: 99%
“…It has been used in the study of the formation of urea in irradiation studies, where its irradiation is shown to lead to the formation of formamide and urea (Ferus et al 2018;Raunier et al 2003Raunier et al , 2004. In addition, it has been shown to be a product of the dissociation of formamide and has even been suggested to be a catalyst for the formation of H 2 in the ISM (Lundell, Krajewska & Räsänen 1998;Duvernay et al 2005;Haupa, Tarczay & Lee 2019). Moreover, there is a clear correlation with the abundances of formamide (Bisschop et al 2007;López-Sepulcre et al 2015).…”
Section: Charged Pathwaymentioning
confidence: 99%
“…[17][18][19][20][21] Many combustion processes are also related to the HNCO species and its derivatives. 7,[22][23][24] Isocyanate molecules are also important interstellar species [4][5][6]25 that are implicated as critical intermediates for prebiotic precursors such as formamide, [26][27][28] thyamine, 29 and urea. 30 One of the reasons isocyanates are so ubiquitous is their diverse and facile reactivity with many organic molecules, 11,17,[31][32][33]33 thus motivating further research into understanding the important features of reactions involving isocyanates.…”
Section: Introductionmentioning
confidence: 99%